LEVELS OF SUBJECTIVE CONTROL OF STUDENTS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Psychology and levels of subjective control have been studied for many years and are an important area of psychological research. This article is devoted to an empirical study of the degree of subjective control in psychology students. The author investigated the levels of subjective control of students using the survey by J. Rotter "The level of subjective control". Empirical data served to reveal the general and structural components of the degree of students' subjective control.